A strategy in the treatment of tendinopathy - Zazirniy, Igor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2011)
The etiology and pathogenesis of tendinopathy remain open to discussion, and its treatment is rather difficult. Recent studies of the inner structures of tendons with help of the technique of microdialysis revealed absence of any signs of the so-called chemical inflammation (the level of prostaglandin 2 was within its normal values) in case of tendinopathy. Studies with help of supersonic diagnostics, colour Doppler and immunohistochemical analysis of biopsy material revealed an increased number of vessels and nerves with substance P and CGRP, a calcitonin gene-bound peptide, in affected tendons versus intact ones. This fact indicates a possibility of the so-called neurogenic inflammation. The area of vascularization in a tendon (with new vessels and nerves), which is detected in case of tendinopathy with help of ultrasonography, is most likely to be the source of pain, and the techniques, both conservative and surgical, which are aimed at destruction of this area, are rather effective.